EVALUATING THE INFLUENCE OF ELECTRONIC GOVERNANCE ON SERVICE DELIVERY IN EBONYI STATE MINISTRIES - Nwanekezi, A. U; Bruno, O.; Oragwu, A. A (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
Effective governance is necessary for meeting the needs of citizens and providing development across the board. In recent times, e-governance has gained increasing acceptance as a political device that leverages information and communication technology (ICT) to improve transparency, provide information speedily to all citizens, and enhance administration efficiency. This article examines the implementation of e-governance in Nigeria and its impact on governance in the country. The concept of e-governance began in the early 1990s and gained popularity in the United States after the 1998 Government Paperwork Elimination Act. Several countries have since followed suit, including Nigeria, which recognized the need to transform the public service into the modern-day system through the use of ICT in the year 2000. E-governance has become an indispensable methodology for ensuring good governance and increased accountability and transparency for better management of resources, growth, and development in Nigeria and beyond. Using several scholarly sources, this article highlights the various benefits of e-governance, including citizen empowerment through access to information, better delivery of government services, and effective government management. The article underscores the important role of ICT, its potential for enhancing governance, and the challenges and ethical considerations inherent in implementing e-governance in rural areas.